A case‐control study of brain structure and behavioral characteristics in 47, XXX syndrome. (27th October 2014) - Lenroot, R. K.; Blumenthal, J. D.; Wallace, G. L.; Clasen, L. S.; Lee, N. R.; Giedd, J. N.
<x xml:space="preserve">Abstract</x> Trisomy X, the presence of an extra X chromosome in females (47, XXX), is a relatively common but under‐recognized chromosomal disorder associated with characteristic cognitive and behavioral features of varying severity. The objective of this study was to determine whether there were neuroanatomical differences in girls with Trisomy X that could relate to cognitive and behavioral differences characteristic of the disorder during childhood and adolescence. MRI scans were obtained on 35 girls with Trisomy X (mean age 11.4, SD 5.5) and 70 age‐ and sex‐matched healthy controls. Cognitive and behavioral testing was also performed. Trisomy X girls underwent a semi‐structured psychiatric interview. Regional brain volumes and cortical thickness were compared between the two groups. Total brain volume was significantly decreased in subjects with Trisomy X, as were all regional volumes with the exception of parietal gray matter. Differences in cortical thickness had a mixed pattern. The subjects with Trisomy X had thicker cortex in bilateral medial prefrontal cortex and right medial temporal lobe, but decreased cortical thickness in both lateral temporal lobes. The most common psychiatric disorders present in this sample of Trisomy X girls included anxiety disorders (40%), attention‐deficit disorder (17%) and depressive disorders (11%). The most strongly affected brain regions are consistent with phenotypic characteristics such as language delay, poor executive function and heightened anxiety previously described in population‐based studies of Trisomy X and also found in our sample.